Proceedings of the Fourth ACM Conference on Wireless Network Security 2011
DOI: 10.1145/1998412.1998414
|View full text |Cite
|
Sign up to set email alerts
|

The communication and computation cost of wireless security

Abstract: The following full text is a publisher's version.For additional information about this publication click this link. http://hdl.handle.net/2066/92444Please be advised that this information was generated on 2024-06-02 and may be subject to change. Article 25fa End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act. This article entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The former indicates the cost of performing cryptographic operations while the latter refers to the cost of transmitting/receiving bits to/from a device. However, several papers have shown that the computation cost is often negligible compared to the communication cost [28,37]. Thus, we propose to use a new optimized message format that is slightly different from the original message format (see Fig.…”
Section: Secure Data Exchangementioning
confidence: 99%
“…The former indicates the cost of performing cryptographic operations while the latter refers to the cost of transmitting/receiving bits to/from a device. However, several papers have shown that the computation cost is often negligible compared to the communication cost [28,37]. Thus, we propose to use a new optimized message format that is slightly different from the original message format (see Fig.…”
Section: Secure Data Exchangementioning
confidence: 99%
“…Assuming a cost of 185nJ/bit for transmitting and 133nJ/bit for receiving [13], the modified EC-A requires approximately 31mJ for a pair wise secret key establishment and hence not energy efficient. In [14] we have proposed an efficient elliptic curve based key establishment technique for WSNs (hereinafter called ECKM) with reduced communication overhead and storage requirement.…”
Section: Algorithm 1 Modified Ec-a Algorithm For Key Establishmentmentioning
confidence: 99%
“…ECDH consumes about 57 mJ on ATMEL MICAz architectures [46] considering both computational and communication overheads. The cost for COKE can be summarized by leveraging the transmission and reception per-bit-cost provided by [47]. In detail, assuming a cost of 185 nJ/bit for transmitting and 133 nJ/bit for receiving, COKE needs 17 mJ in order to establish a 96 bits secret key.…”
Section: Coke Energy Budgetmentioning
confidence: 99%